ANALYSIS OF THE CONTENT OF PSYCHOLOGICAL COMPETENCE OF A HISTORY TEACHER IN THE CONDITIONS OF WAR AND IN THE POST-WAR PERIOD - Oleksenko, Svitlana (SWorld-Ger Conference proceedings, 2023)
The relevance of psychological knowledge and skills, the development of the psychological competence of a history teacher during the war period is analyzed. Psychological competence is considered as a structural element of a teacher’s professional compete